The Implications of Intellectual Property as Objects of Fiduciary Guarantee for Creative Economy Entrepreneurs - Rina Talisa; Siti Malikhatun Badriyah (Jurnal Daulat Hukum, 2023)
Intellectual Property (IP) as objects of fiduciary security has not been implemented optimally in financing institutions in practice. In banking practices, the use of IP will cause problems when defaults occur or many debtors are unable to meet the legal obligation of debt repayment. The legal problems that occur related to intellectual property issues as fiduciary security are an obstacle and challenge that the government needs to fix in strengthening the rules that form the basis of intellectual property as an object of fiduciary security, especially for creative economy actors. This study aims to analyze the legal standing of IP as objects of fiduciary security in financing institutions and to analyze the application of IP to the banking sector to creative economic actors in obtaining credit. The research method that is used in this research is a normative juridical method. The research shows that the regulation regarding IP as fiduciary security is regulated by Article 16 (3) of Act No. 28 of 2014 on Copyright and Article 108 (3) of Act No. 13 of 2016 on Patents. A copyright must be registered first at the Directorate General of Intellectual Property if it is to be used as a fiduciary security because without registration there will be no fiduciary security. With the existence of IP as a fiduciary security, banking institutions with the government need to make improvements and policy breakthroughs to the laws and regulations that are adjusted to the implementing regulations related to the implementation of the imposition of IP objects as fiduciary security.